2018
DOI: 10.1101/403220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oncogenic activation of Nrf2 by specific knockout of Nrf1α that acts as a dominant tumor repressor

Abstract: HIGHLIGHTS  Opposing and unifying inter-regulatory cross-talks between Nrf1 and Nrf2  Malignant growth of Nrf1 / -derived tumor is prevented by silencing Nrf2  Hyper-activation of Nrf2 by Nrf1 / results from decreased Keap1 and PTEN  Nrf1 / -tumor is repressed by Nrf2 /TA , but unaltered by its active caNrf2 ΔN SUMMARY Liver-specific knockout of Nrf1 in mice leads to non-alcoholic steatohepatitis with dyslipidemia, and its deterioration results in spontaneous hepatoma, but the underlying mecha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
(114 reference statements)
2
3
0
Order By: Relevance
“…The western blotting result showed that NFE2L1 knockdown could efficiently elevate the expression of NFE2L2, HMOX1, and PTGS2 and decrease kelch like ECH associated protein 1 (KEAP1) (Fig. 4F), which were consistent with our previous results (Qiu et al, 2018). Then the changes in the protein levels of the key enzymes of sugar metabolism were detected.…”
Section: Nfe2l1 Deficiency Results In the Reprogramming Of Glucose Metabolism And Exacerbates The Warburg Effectsupporting
confidence: 90%
See 4 more Smart Citations
“…The western blotting result showed that NFE2L1 knockdown could efficiently elevate the expression of NFE2L2, HMOX1, and PTGS2 and decrease kelch like ECH associated protein 1 (KEAP1) (Fig. 4F), which were consistent with our previous results (Qiu et al, 2018). Then the changes in the protein levels of the key enzymes of sugar metabolism were detected.…”
Section: Nfe2l1 Deficiency Results In the Reprogramming Of Glucose Metabolism And Exacerbates The Warburg Effectsupporting
confidence: 90%
“…In NFE2L1 knockdown cells, the ROS level was increased more than 6 times in comparison with the control group after glucose deprivation for 6 hours, indicating the high levels of oxidative damage of NFE2L1 knockdown cells. These results were in accordance with previous studies that glucose starvation resulted in strong oxidative stress to induce cell death after NFE2L1 knockout (Qiu et al, 2018;Zhu et al, 2020).…”
Section: Nfe2l1 Deficiency Disrupts Cellular Energy Metabolism Signals and Induces Cell Death By Glucose Starvationsupporting
confidence: 94%
See 3 more Smart Citations